Inclusive Education Innovation: Building Learning Spaces for All - Nasution, Habib Syukri (Indonesian Journal Education, 2025)
clusive education is a strategic approach to ensuring justice and equity in educational access for all learners, including those with special needs. This article aims to explore various innovations in inclusive education practices, both theoretical and practical, with a focus on global, national, and local contexts—particularly in North Sumatra, Indonesia. The study draws on developmental theories (Bronfenbrenner, Piaget, Vygotsky), constructivism (Bruner), Universal Design for Learning (UDL), and social justice frameworks to analyze effective strategies for creating adaptive and participatory learning environments. Findings indicate that although Indonesia has inclusive education policies in place, challenges such as the shortage of special education teachers, limited disability-friendly infrastructure, and low public awareness continue to hinder implementation. A case study in North Sumatra reveals that regulations like Regional Regulation No. 29 of 2016 provide a legal foundation, yet practical application still requires strengthened human resources and adequate facilities. Therefore, cross-sector collaboration and continuous innovation are essential to realizing truly inclusive learning spaces for all students.